F Formulasi Dan Stabilitas Krim Kutu Air Ekstrak Rimpang Lengkuas (Alpina galanga L) Dengan Variasi Tween 80 Dan Span 60 Sebagai Emulgator - Maleh, Arie; Budi, Setia; Audina, Mia; Noval, Noval (Jurnal Pelayanan Kefarmasian dan Sains, 2024)
Background: Water fleas are an infectious disease caused by dermatophyte fungi which infect the skin between the toes, soles of the feet and the lateral parts of the feet. Galangal rhizome (Alpinia galanga L) has various properties, including being an antifungal. Cream is a semi-solid preparation and contains one or more medicinal substances dissolved or distributed as a base. Cream has amphipathic properties which have parts that can dissolve polar and non-polar compounds. This amphipathic property is found in the emulsifier in cream preparations. Emulgator Tween 80 and Span 60 are included in the class of surfactant emulsifiers chosen because they are not irritating and non-toxicObjective: To determine the effect of varying concentrations of Tween 80 and Span 60 emulsifiers on the physicochemical evaluation and stability of galangal rhizome extract athlete's foot cream preparations.Methods: The method used was experimental with a quasi-experimental design with a pretest- posttest control group design research design. Simplicia was made into a thick extract, then athlete's foot cream was made and continued with accelerated physicochemical and stability evaluations using the cycling test method. Data were analyzed using one way anova.Results: The results of the evaluation of athlete's foot cream with galangal rhizome extract with variations of tween 80 and span 60 met the evaluation and stability test requirements for the cream preparation.Conclusion: From the results of the physicochemical evaluation and stability of the galangal rhizome extract athlete's foot cream, all formulations have met the cream preparation test requirements.